Volatilization of standalone dicamba and dicamba plus glyphosate as function of volatility reducer and different surfaces - Carbonari, Caio A. [UNESP]; Costa, Renato N. [UNESP]; Bevilaqua, Natalia C. [UNESP]; Pereira, Vinicius G.C. [UNESP]; Giovanelli, Bruno F. [UNESP]; Lopez Ovejero, Ramiro F.; Palhano, Matheus; Barbosa, Henrique; Velini, Edivaldo D. [UNESP] (MDPI, 2020)
Dicamba is a herbicide with a moderate volatility profile. Such volatility behavior can be significantly diminished with formulation technology and volatilization reducers. The objective of this study was to quantify the volatility potential of dicamba diglycolamine salt (DGA) in a standalone application or in tank mixture with glyphosate (potassium salt) (GK), with and without volatilization reducer (acetic acid-VaporGrip®) from different surfaces. The combination of these products was applied on four different surfaces (glass slides, corn straw, and dry and moist sandy soil) with three replications, and the experiment was duplicated. The application was performed indoors with an automated sprayer. After application, targets were positioned in cartridges containing two filters in series. Cartridges were placed in a vapor collection system that consisted of a chromatographic oven with constant temperature of 40 °C attached to a vacuum pump for 24 h. After this period, liquid samples were obtained from an extraction procedure of filters and surfaces, which corresponded to the volatilized and deposited portions of the herbicides, respectively. The samples were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The use of this method provided a rapid and consistent evaluation, in which the treated surface exerts a direct influence on the amount of volatilized dicamba. The mixture of dicamba and glyphosate solutions exhibited different volatility profiles as a function of the treated surfaces. The DGA applied alone had the largest level of volatility when applied on moist soil and the lowest level of volatility in dry soil and straw. The DGA with GK had volatilities similar in dry soil, wet soil and straw. The volatility reducer in the tank mixture was effective in reducing DGA dicamba volatilization, regardless of the sprayed surface and the tank mixture, making the application of dicamba safer from the volatilization standpoint.
Keywords: Adjuvants; Diglycolamine salt (DGA); Soil; Straw; Vapor